Hachune Miku's everyday Vocaloid paradise!. 1 - Ontama; Scoble, Rebecca; Sentar, Lianne (Seven Seas Entertainment, LLC, 2017)
Contains a collection of comedic short comics featuring Hatsune Miku-spinoff character, the pigtailed Hachune Miku.